Impacts of Climate Change on Inequities in Child Health - Charmian M. Bennett; Sharon Friel (MDPI AG, 2014)
This paper addresses an often overlooked aspect of climate change impacts on child health: the amplification of existing child health inequities by climate change. Although the effects of climate change on child health will likely be negative, the distribution of these impacts across populations will be uneven. The burden of climate change-related ill-health will fall heavily on the world's poorest and socially-disadvantaged children, who already have poor survival rates and low life expectancies due to issues including poverty, endemic disease, undernutrition, inadequate living conditions and socio-economic disadvantage. Climate change will exacerbate these existing inequities to disproportionately affect disadvantaged children. We discuss heat stress, extreme weather events, vector-borne diseases and undernutrition as exemplars of the complex interactions between climate change and inequities in child health.